SGH-NTU collaboration - NTU-SGH Annual Biomedical Engineering Symposia (2008)
Many collaborative Biomedical Engineering Research Projects were initiated with participation from doctors at Singapore General Hospital and engineers at Nanyang Technological University. The results of some of these joint projects are reported in the five NTU-SGH Annual Biomedical Engineering Symposia .The publications at these Symposia are included in the report.